Seizures with Pentylenetetrazoll Indling Cause a Decrease in the Number of Pyramidal Neurons in the Rat Hippocampus - Kocacan, Suleyman Emre; Sefil, Fatih; Elibol, Ebru; Altunkaynak, Berrin Z.; Acar, Meryem Dilek; Bagirici, Faruk; Kaplan, Süleyman (Sci Printers & Publ Inc, 2016)
OBJECTIVE: To investigate the effects of pentylenetetra-zole (PTZ) kindling on the number of pyramidal neurons in the rat hippocampus. STUDY DESIGN: Using unbiased stereology, we calculated total pyramidal neuron numbers in the CA1, CA2, and CA3 areas and the whole hippocampus after PTZ-induced kindling. The estimation and the analysis of the number of hippocampal pyramidal cells (areas of CA1-3) were done with the optical fractionator technique, which is a stereological counting technique. RESULTS: Stereological analysis showed that the total number of pyramidal neurons in the whole hippocampus and the number of pyramidal neurons in CA1 were significantly lower in kindled rats as compared to the controls (p<0.05). However, no significant difference was found in the neuron numbers of CA2 and CA3 (p>0.05). CONCLUSION: PTZ-induced seizures cause a decrease in the amount of pyramidal neurons in the CA area of the rat hippocampus.
Keywords: Convulsants; Epilepsy; Kindling; Neurologic; Neurological Disorders; Neurotoxin Diseases; Neurotoxicity; Neurotoxicity Syndromes; Pentylenetetrazole; Seizures; Stereology